Lower-serum P1NP/βCTX ratio and hypoalbuminemia are independently associated with osteoporotic nonvertebral fractures in older adults - Fisher A (Dove Medical Press, 2017)
Alexander Fisher,1–3 Wichat Srikusalanukul,1 Leon Fisher,4 Paul N Smith2,3 1Department of Geriatric Medicine, The Canberra Hospital, ACT Health, Canberra, Australia; 2Department of Orthopaedic Surgery, The Canberra Hospital, ACT Health, Canberra, Australia; 3Australian National University Medical School, Canberra, ACT, Australia; 4Department of Gastroenterology, Frankston Hospital, Peninsula Health, Melbourne, Australia Purpose: To estimate the discriminative value of serum P1NP/βCTX ratio and albumin levels in hospitalized orthogeriatric patients with and without nonvertebral fractures. Methods: In 1,239 orthogeriatric patients (mean age 78.1±9.52 years, 69.1% women) including 854 (68.9%) with osteoporotic nonvertebral fractures (455 [36.7%] with hip fracture [HF]) and 385 (31.1%) without fractures, markers of bone formation (procollagen type 1 N-terminal propeptide [P1NP], osteocalcin [OC], and bone resorption (beta-C-terminal cross-linking telopeptide of type 1 collagen [βCTX]), indices of mineral metabolism, and parameters of liver and renal functions were assessed; data on clinical and laboratory characteristics were collected prospectively. Results: Both lower serum P1NP/βCTX ratio and albumin concentration (as continuous or categorical variables) were independently associated with fracture presence in multivariate logistic regressions. Compared with the highest P1NP/βCTX tertile, the prevalence of HF, after adjustment for multiple covariates, was 3-fold higher in the lowest tertile and 1.5 times higher in the middle tertile; presence of any fracture was 2.3- and 1.6-fold higher, respectively; patients with albumin levels in the lowest tertile had multivariate odds ratio (OR) of 4.6 for HF and 2.8 for any fracture, in the middle tertile the ORs were 2.2 and 1.3, respectively. The P1NP/βCTX <100.0 (median) and hypoalbuminemia (<33 g/L) demonstrated area under the curve values for HF of 0.802 and 0.806, respectively, and for any fractures of 0.711 and 0.706, respectively. When both characteristics were combined, the ORs for HF or any fracture, compared with the nonfractured group, were 7.8 and 3.2, respectively, with an accuracy of 79.6% and 71.6%, respectively. Conclusions: In orthogeriatric patients, both serum P1NP/βCTX ratio and albumin levels demonstrated an inverse dose–effect relationship with the prevalence of nonvertebral fractures and independently indicated fracture presence with acceptable discriminatory power. Lower P1NP/βCTX (<100) and hypoalbuminemia could be useful simple additive prognostic tools for fracture risk stratification in the elderly. Keywords: nonvertebral fractures, P1NP/βCTX ratio, albumin, elderly, orthopedic patients